2016
DOI: 10.1111/mcn.12294
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Baby‐friendly Hospital Initiative on breastfeeding and child health outcomes: a systematic review

Abstract: The Baby-friendly Hospital Initiative (BFHI) is a key component of the World Health Organization/United Nations Children's Fund Global Strategy for Infant and Young Child Feeding. The primary aim of this narrative systematic review was to examine the impact of BFHI implementation on breastfeeding and child health outcomes worldwide and in the United States. Experimental, quasi-experimental and observational studies were considered eligible for this review if they assessed breastfeeding outcomes and/or infant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
386
2
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(433 citation statements)
references
References 89 publications
(160 reference statements)
16
386
2
12
Order By: Relevance
“…25,26 Additionally, feeding is of prevalent concern for parents as preterm infants often have difficulty establishing breastfeeding and may require expressed breastmilk or oral supplemental feeding. 27,28 It is essential that parents are provided with accurate information when they need it: too much information may cause anxiety, while too little may create fear. 7 Information seeking by parents whose infant is in the NICU, whether online, through health professionals, or through peers, is thought to stem from a need to control the situation and is a method of engaging in care of their infant.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Additionally, feeding is of prevalent concern for parents as preterm infants often have difficulty establishing breastfeeding and may require expressed breastmilk or oral supplemental feeding. 27,28 It is essential that parents are provided with accurate information when they need it: too much information may cause anxiety, while too little may create fear. 7 Information seeking by parents whose infant is in the NICU, whether online, through health professionals, or through peers, is thought to stem from a need to control the situation and is a method of engaging in care of their infant.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these problems with postnatal care, increasing proportions of women reported that they received consistent advice and support with infant feeding reflecting the work that has been put into this aspect of care (Perez-Escamilla et al, 2016). Overall, the vast majority of women said that staff treated them with respect, although less so in the postnatal period compared to antenatal and intrapartum care, and overall, women indicated consistently high satisfaction with their care.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Mothers who room-in are better able to learn and detect their infants’ hunger cues 12 and are more likely to be exclusively breastfeeding at hospital discharge. 13,14 Studies have also suggested that rooming-in facilitates mother-infant bonding, which, in turn, positively influences breastfeeding. 15 Furthermore, rooming-in promotes family-centered care as the infant is not taken away for pediatric rounds and other routine procedures.…”
Section: Introductionmentioning
confidence: 99%